ANALISIS STRATEGI EKSPANSI PEMASARAN GLOBAL DALAM KEBIJAKAN PRODUK - Nadya Maulidya M; Nabillah Purba; Nurbaina Junita S; sri lestari; Zerimah Hasibuan; Suhairi Suhairi (OPTIMAL Jurnal Ekonomi dan Manajemen, 2023)
The purpose of this study is to examine the various stages of global marketing development or expansion plans in global product policies. By using a descriptive qualitative analysis method, which uses the results of data from various reference sources to describe a research result. Part of the study of the literature involves organizing research resources, reading and taking notes, and using library data collection methods. Six considerations in global product policy are presented in this study, including producing new products for global markets, standardization versus customization, international diffusion, developing new products for global markets, and developing truly global products. In addition, there are five tactics for expanding global marketing: product communication expansion, product communication expansion adaptation, product adaptation, multiple adaptation, and product purpose.